Follicular Proliferative Lesion Arising in Struma Ovarii - Min Jee Park; Min A Kim; Mi Kyung Shin; Hye Sook Min (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Malignant struma ovarii is extremely rare and difficult to diagnose histologically, particularly in cases of follicular carcinoma. This case study is intended to describe three cases of follicular proliferative lesion arising in struma ovarii that we experienced. The first case was clearly malignant given the clinical picture of multiple recurrences, but there was little histological evidence of malignancy. Our second case featured architectural and cellular atypia and necrosis and was diagnosed as malignant despite the absence of vascular and stromal invasion. Our third case exhibited solid microfollicular proliferation without any definite evidence of malignancy (even the molecular data was negative); however, we could not completely exclude malignant potential after conducting a literature review. In cases such as our third case, it has been previously suggested that a diagnostic term recognizing the low-grade malignant potential, such as "proliferative stromal ovarii" or "follicular proliferative lesion arising in the stromal ovarii" would be appropriate.